Inge Grognard, Ronald Stoops. - Stoops, Ronald; Grognard, Inge; Cauvin, Jean Paul; Debo, Kaat; Judah, Hettie; Lutens, Serge; Margiela, Martin; van Beirendock, Walter; Vandevorst, An; Arickx, Filip; Van Saene, Dirk (Gent : Ludion, 2010)
Anthology of over 30 years of collaboration between Belgian photographer Ronald Stoops and his wife make-up artist Inge Grognard, with emphasis placed on the duo’s non-commercial work, including projects with other like-minded people such as Narcisse Tordoir, Martin Margiela, A.F. Vandevorst, Jurgi Persoons and Andrea Cammarosano. Inge and Ronald started their careers in the early 1980’s, coinciding with the international breakthrough of Belgian Fashion. As if so often the case in fashion, group dynamics proved to be a crucial factor, with designers surrounding themselves with other creative people: stylists, photographers, graphic designers and make-up artists who act as a catalyst for each other’s professional, international and individual careers. This also goes for Inge and Ronald. Back in their early days they made valuable contributions to the imagery of Dries Van Noten, Dirk Bikkembergs, Walter Van Beirendonck, Dirk Van Saene and Martin Margiela amongst others. The second generation of Belgian designers including Raf Siomins, Veronique Branquinho, A.F. Vandevorst and Jurgi Persoons have also found Grognard and Stoops strong visual language invaluable.
boek